Change in lignin structure, but not in lignin content, in transgenic poplar overexpressing the rice master regulator of secondary cell wall biosynthesis. Issue 2 (1st February 2018) - Nuoendagula,; Tsuji, Yukiko; Takata, Naoki; Sakamoto, Shingo; Nakagawa‐Izumi, Akiko; Taniguchi, Toru; Ralph, John; Mitsuda, Nobutaka; Kajita, Shinya
Abstract : We previously succeeded in enhancing wood formation of wood in transgenic poplar plants by overexpressing secondary wall NAM/ATAF/CUC (NAC) domain protein 1 from Oryza sativa ( OsSWN1 ), a transcription factor 'master regulator' of secondary cell wall formation in rice, under control of the fiber preferential NST3/SND1 promoter from Arabidopsis. Transgenic plants had an increased cell wall thickness and cell wall density of individual cells in the secondary xylem of stems as well as an increased wood density. OsSWN1 triggers the induction of polysaccharide and lignin biosynthetic gene expressions, however, resulting in no significant impact on the lignin content in the transgenic plants. In contrast, wet and dry chemical analyses of lignin revealed changes in S/G ratio and in the composition of lignin interunit linkages in transgenic lines. The results from gene expression analysis suggest that the structural changes in lignin were due to an unbalanced induction of lignin biosynthetic genes in transgenic lines. Our present data indicate that the overexpression of the chimeric transcription factor causes accelerated deposition of secondary cell wall components including lignin and polysaccharides through an acquired mechanism.